Efficacy of emamectin benzoate against fruit borer, Helicoverpa armigera in tomato - ., Lekha; Ameta, O P; Swami, Hemant; Dangi, N L (Indian Journal of Plant Protection, 2020)
Field experiments conducted on relative efficacy of emamectin benzoate 1.9% E.C at different concentrations (0.05, 0.06, 0.07 and 0.08%) along with lambda-cyhalothrin 5% EC (0.06%) and chlorantraniliprole 18.5 % EC (0.03%) against Helicoverpa armigera (Hub.) in tomato during 2013-04 and 2014-15 revealed that all the three insecticides were significantly superior to untreated control in reducing H. armigera infestation in tomato. However, emamectin benzoate 1.9% EC (0.08%) caused significantly higher reduction in the population of larvae and lowest fruit damage than the remaining treatments during both the years. The marketable yield recorded in emamectin benzoate 1.9% EC (0.08%) was also significantly higher than that recorded in other treatments. The insecticidal treatments were safe to coccinellids and Chrysopa and did not have any phytotoxic effect.